2020
DOI: 10.1007/s11010-020-03715-9
|View full text |Cite
|
Sign up to set email alerts
|

Global profile changes in transcripts induced with a phosphate analogue: implications for gene regulation

Abstract: Previous work has shown that thiophosphate, a phosphate analogue, leads to a global shift in the distribution of cellular proteins in a variety of organisms. Thiophosphate, when added to culture media, gets incorporated into the nucleic acids of cells resulting in nuclease-resistant phosphorothioate linkages. Using Escherichia coli, as a model organism, it was found that the global changes in protein expression induced with thiophosphate could be accounted for by significant changes in the absolute transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…More recently my own research has found that use of the phosphate analogue, thio-phosphate, during cell culture appears to result in an increase in the cellular energy charge [1]. This analogue reduces RNA turnover by creating phosphorothioate linkages in RNA that inhibit cellular nucleases, which then allows the accumulation of significant amounts of mRNA and other non-ribosomal RNA in the cell.…”
Section: Phosphate Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently my own research has found that use of the phosphate analogue, thio-phosphate, during cell culture appears to result in an increase in the cellular energy charge [1]. This analogue reduces RNA turnover by creating phosphorothioate linkages in RNA that inhibit cellular nucleases, which then allows the accumulation of significant amounts of mRNA and other non-ribosomal RNA in the cell.…”
Section: Phosphate Analoguesmentioning
confidence: 99%
“…In E. coli dramatic morphological changes are also observed using thio-phosphate instead of phosphate in culture media [1]. Namely, the bacteria form extensive filaments.…”
Section: Phosphate Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiophosphate, a phosphate analogue, can be used to enhance cellular biosynthesis and thereby serve as a potential archetype for cell differentiation 1,2 . The analogue likely induces these changes by increasing the cellular energy charge or state in simple cells like bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thiophosphate reduces RNA turnover by creating phosphorothioate linkages in RNA that inhibit cellular nucleases. The energy savings from reduced RNA turnover in Escherichia coli (E. coli) appears to enable an enhanced biosynthetic profile the result of transcriptional changes rather than differential mRNA stabilization 1,2 . Previous studies demonstrate that biosynthetic activity at later stages of growth show enhancements in the transcription of genes for RNA processing enzymes, ribosomal proteins, tRNA charging enzymes, translational proteins, as well as outer membrane, plasma membrane, and periplasmic proteins 1 .…”
Section: Introductionmentioning
confidence: 99%